Trace Metal Contents of Higher Fungi from ZiganaHighland in Turkey - SESLI, ERTUGRUL (Asian Journal of Chemistry, 2010)
Higher fungus specimens were collected from Zigana Highland at East Black Sea Region of Turkey. The specimens were observed under microscope, photographed and deposited in a personal fungarium at the Black Sea Technical University in Trabzon, Turkey. As a result of field and laboratory studies, 14 higher fungus taxa (Lepiota clypeolaria, Leucoagaricus leucothites, Agaricus arvensis, Coprinus atmmentarius, Amanita pantherina, Amanita fmnchetii, Panaeolus acuminatus, Entoloma sinuatum, Entoloma chalybaeum, Clitopilus prunu/us, Tricholomopsis rutilans, Tricholoma virgatum, Tricholoma terreum, Tricholoma imbricatum) were recorded. Trace metal contents of specimens were determined by atomic absorption spectrometry after microwave digestion. The results were (in mg/kg) 25-153 iron, 9.3-40.4 copper, 10.6-36 manganese, 30.7-168 zinc, 13.2-330 aluminium and 0.2-9.2 lead.